phân tích đa thức thành nhân tủ: \(x^6+x^3+1\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
x3 - 2x2 + 2x2 - 4x - 2x +4
x2 ( x - 2 ) +2x (x - 2 ) + 2 (x -2 )
(x -2) (x2 + 2x + 2 )
(x - 2) (x + 1 )2
![](https://rs.olm.vn/images/avt/0.png?1311)
a) x3 - 4x2 + 12x - 27 = (x - 3)(x2 + 3x + 9) - 4x(x - 3)
= (x - 3)(x2 + 3x + 9 - 4x) = (x - 3)(x2 - x + 9)
b) x3 + 2x2 + 2x + 1 = (x + 1)(x2 - x + 1) + 2x(x + 1)
= (x + 1)(x2 - x + 1 + 2x) = (x + 1)(x2 + x + 1)
c) y4 - 2y3 + 2y - 1 = (y2 - 1)(y2 + 1) - 2y(y2 - 1)
= (y2 - 1)(y2 + 1 - 2y) = (y - 1)(y + 1)(y - 1)2
= (y + 1)(y - 1)3
![](https://rs.olm.vn/images/avt/0.png?1311)
Sửa đề: \(\left(x-1\right)\left(x+2\right)\left(x+3\right)\left(x+6\right)-28\)
\(=\left(x-1\right)\left(x+6\right)\left(x+2\right)\left(x+3\right)-28\)
\(=\left(x^2+5x-6\right)\left(x^2+5x+6\right)-28\)
\(=\left(x^2+5x\right)^2-64\)
\(=\left(x^2+5x+8\right)\left(x^2+5x-8\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(1,\\ a,=4\left(x-2\right)^2+y\left(x-2\right)=\left(4x-8+y\right)\left(x-2\right)\\ b,=3a^2\left(x-y\right)+ab\left(x-y\right)=a\left(3a+b\right)\left(x-y\right)\\ 2,\\ a,=\left(x-y\right)\left[x\left(x-y\right)^2-y-y^2\right]\\ =\left(x-y\right)\left(x^3-2x^2y+xy^2-y-y^2\right)\\ b,=2ax^2\left(x+3\right)+6a\left(x+3\right)\\ =2a\left(x^2+3\right)\left(x+3\right)\\ 3,\\ a,=xy\left(x-y\right)-3\left(x-y\right)=\left(xy-3\right)\left(x-y\right)\\ b,Sửa:3ax^2+3bx^2+ax+bx+5a+5b\\ =3x^2\left(a+b\right)+x\left(a+b\right)+5\left(a+b\right)\\ =\left(3x^2+x+5\right)\left(a+b\right)\\ 4,\\ A=\left(b+3\right)\left(a-b\right)\\ A=\left(1997+3\right)\left(2003-1997\right)=2000\cdot6=12000\\ 5,\\ a,\Leftrightarrow\left(x-2017\right)\left(8x-2\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=2017\\x=\dfrac{1}{4}\end{matrix}\right.\\ b,\Leftrightarrow\left(x-1\right)\left(x^2-16\right)=0\Leftrightarrow\left[{}\begin{matrix}x=1\\x=4\\x=-4\end{matrix}\right.\)
![](https://rs.olm.vn/images/avt/0.png?1311)
x^2 - y^2 - 2x + 4y - 3
= (x^2 - 2x + 1) - (y^2 - 4y + 4)
= (x + 1)^2 - (y + 2)^2
= (x + 1 - y - 2)(x + 1 + y + 2)
= (x - y - 1)(x + y + 3)
\(x^6+x^3+1=\left(x^6+2x^3+1\right)-x^3\)
\(=\left[\left(x^3\right)^2+2x^3.1+1^2\right]-\left(x\sqrt{x}\right)^2\)
\(=\left(x^3+1\right)^2-\left(x\sqrt{x}\right)^2\)
= \(\left(x^3-x\sqrt{x}+1\right)\left(x^3+x\sqrt{x}+1\right)\)